Advances in Practical Applications of Agents and Multiagent Systems 8th International Conference on Practical Applications of Agents and Multiagent Systems (PAAMS 2010) - Demazeau, Yves.; Dignum, Frank.; Corchado, Juan M.; Přez, Javier Bajo. (Advances in Intelligent and Soft Computing,, 2010)
PAAMS, the International Conference on Practical Applications of Agents and Multi-Agent Systems is an international yearly stage to present, to discuss, and to disseminate the latest advances and the most important outcomes related to real-world applications. It provides a unique opportunity to bring multi-disciplinary experts, academics and practitioners together to exchange their experience in the development of Agents and Multi-Agent Systems. This volume presents the papers that have been accepted for the 2010 edition. These articles capture the most innovative results and this year<U+0019>s advances. Each paper has been reviewed by three different reviewers, from an international com-mittee composed of 82 members from 26 different countries. From the 66 submissions received, 19 were selected for full presentation at the conference, and 14 were accepted as short papers. Moreover, PAAMS'10 incorporated special sessions and workshops to complement the regular program, which included 85 accepted papers.